A slow-release rust-proof negative carbon regenerated concrete material and its preparation method and application
By loading the rust resistor into the recycled concrete micro powder/agglomerate, and using wet carbonization to generate nano calcium carbonate and silica gel, the problems of insufficient durability of recycled concrete and high cost of rust resistor carrier in the prior art are solved, and efficient and durable sustained release rust-retardant carbon recycled concrete materials are achieved.
Patent Information
- Application Number
- CN202311198070.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-18
AI Technical Summary
In the prior art, reinforced concrete structures have insufficient durability in a chloride-salt environment, and conventional rust resistors are quickly lost, interfering with cement hydration, and the carrier preparation cost is high and energy consumption is large, resulting in the recycled concrete being inferior to ordinary concrete in terms of mechanical properties and corrosion resistance.
Recycled concrete micropowder/aggregate is used as the rust inhibitor carrier, and the rust inhibitor is loaded into the recycled concrete material through soaking and wet carbonization to achieve a sustained release effect, and the material performance is enhanced by the formation of nano calcium carbonate and silica gel.
The compressive strength and durability of recycled concrete are improved, and the efficient utilization and sustained release of rust resistors are achieved. At the same time, the physical and mechanical properties of the concrete matrix are optimized, and the capture and utilization of CO2 are achieved.
Smart Images

Figure CN117142788B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete, and in particular to a slow-release rust-resistant negative carbon regenerated concrete material and a preparation method and application thereof. Background Art
[0002] The insufficient durability of reinforced concrete structures in chloride environments leads to a significant shortening of the structural service life. Taking effective anti-corrosion measures can not only ensure the safe service of reinforced concrete structures within the designed service life, but also avoid high carbon emissions caused by repair and maintenance.
[0003] Steel bar rust inhibitors are widely used to improve the durability of reinforced concrete structures because of their convenient construction and economic effectiveness. Conventional rust inhibitors such as nitrites and amino alcohols are easily lost in concrete, resulting in their lack of long-term effectiveness. In addition, rust inhibitors added to concrete will interfere with the cement hydration process, have side effects on the concrete matrix, and affect the physical and mechanical properties of concrete. The use of suitable carriers to load rust inhibitor molecules can not only achieve efficient utilization of rust inhibitors but also solve their negative impact on the concrete matrix. In the prior art, rust inhibitor carriers include inorganic and organic materials such as microcapsules and layered bimetallic oxides. However, existing rust inhibitor carriers have problems such as high preparation cost and high energy consumption, which limits their practical application in bulk concrete materials.
[0004] Using waste concrete to prepare concrete materials can effectively solve the problem of low utilization rate of construction solid waste. However, concrete prepared with recycled concrete aggregate / micropowder is inferior to ordinary concrete in mechanical properties, resistance to chloride ion corrosion, impermeability, and carbonization resistance. When corrosive media invade, recycled concrete cannot effectively protect the internal steel bars. The problem of insufficient durability seriously restricts the application of recycled concrete in long-life structures and structures in harsh corrosive environments. Existing methods for modifying recycled concrete materials include physical strengthening, chemical modification, nano-modification, dry carbonization, etc. The modification effect is limited to the concrete matrix, and the modified concrete still has a gap in performance compared to ordinary concrete. Summary of the invention
[0005] The purpose of the present invention is to provide a slow-release rust-resistant negative carbon regenerated concrete material and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is to provide a rust-resistant recycled concrete material, which is obtained by loading a rust inhibitor on the recycled concrete material and then carbonizing it.
[0008] In the present invention, the recycled concrete material includes recycled concrete powder (particle size <75 μm), fine aggregate (particle size 0.6-1.18 mm) or coarse aggregate (particle size 1.18-3.36 mm).
[0009] The second technical solution of the present invention is to provide a method for preparing the above-mentioned rust-resistant recycled concrete material, comprising the following steps:
[0010] The recycled concrete material is soaked in an organic / inorganic rust inhibitor solution, and then the soaked recycled concrete material is carbonized by a wet carbonization method, and the rust-resistant recycled concrete material is obtained after filtering.
[0011] As a further preferred embodiment of the present invention, the mass concentration of the rust inhibitor solution is 10-30%, and the immersion time is not less than 48 hours, more preferably 72 hours.
[0012] As a further preferred embodiment of the present invention, the carbon dioxide flow rate of the wet carbonization method is 0.1-0.5 L / min, and the carbonization temperature is 20-30° C. More preferably, the purity of the carbon dioxide is not less than 90%.
[0013] As a further preferred embodiment of the present invention, during the treatment process of the wet carbonization method, the recycled concrete material loaded with rust-inhibiting molecules is added into deionized water at a mass fraction of 5%.
[0014] As a further preferred embodiment of the present invention, the carbonization time of the wet carbonization method is 20-120 min; more preferably 20-60 min.
[0015] As a further preferred embodiment of the present invention, a drying step is further included after filtration. The drying method used is freeze drying, and more preferably, the freeze drying temperature is -50°C and the time is 24 hours.
[0016] The third technical solution of the present invention is to provide the application of the above-mentioned rust-resistant recycled concrete material in concrete preparation.
[0017] The fourth technical solution of the present invention is to provide a concrete comprising the above-mentioned rust-resistant recycled concrete material.
[0018] As a further preferred embodiment of the present invention, the above-mentioned rust-resistant recycled concrete material is used to replace 40-100% Vol of aggregate in the concrete.
[0019] As a further preferred embodiment of the present invention, the water-cement ratio of the concrete is 0.3-0.65, and the cement-sand ratio is 1:2-1:3.
[0020] The present invention discloses the following technical effects:
[0021] Recycled concrete materials have the characteristics of high porosity and high water absorption, and are potential excellent carriers of rust-inhibiting molecules. The present invention loads the rust-inhibiting molecules into recycled concrete aggregate / micropowder, which can avoid the direct interaction between the rust-inhibiting molecules and cement paste to affect cement hydration, thereby affecting the physical and mechanical properties of the concrete matrix.
[0022] In view of the problems of high cost and high energy consumption in preparing rust-inhibiting molecular carriers, as well as the limitations of recycled concrete modification methods, the present invention proposes a method for efficiently and conveniently preparing slow-release rust-inhibiting negative carbon recycled concrete materials: recycled concrete powder / aggregate is used as a rust-inhibiting molecular carrier to load the rust-inhibiting molecules, and a simple wet carbonization method is used to pretreat the surface of the recycled concrete material to seal the loaded rust-inhibiting molecules and ensure the slow release of the rust-inhibiting molecules. At the same time, nano-calcium carbonate and silica gel generated on the surface by wet carbonization play a "crystal nucleus" and "volcanic ash" effect in fresh concrete, enhance the performance of recycled aggregate / powder and the interface performance with fresh concrete, optimize the performance of the interface transition zone, improve the performance and durability of recycled concrete, and realize CO2 capture and utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is a diagram showing the preparation mechanism of the slow-release rust-resistant negative carbon regenerated concrete material of the present invention;
[0025] Figure 2 TG-DTG test curve of the raw recycled concrete aggregate and the slow-release rust-resistant negative carbon recycled concrete material in Example 1 of the present invention;
[0026] Figure 3 The compressive strength results of the slow-release rust-resistant negative carbon regenerated concrete materials prepared in Examples 1-2 and Comparative Example 1 of the present invention;
[0027] Figure 4 FTIR graph (a), XRD graph (b), TG test result (c) of the slow-release rust-resistant negative carbon regenerated concrete material prepared in Examples 1-2 and Comparative Example 1 of the present invention, and the test result of the electrical conductivity (d) of the regenerated mortar obtained in Examples 3-4 and the control group. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0033] Figure 1 This is a diagram of the preparation mechanism of the slow-release rust-resistant negative carbon regenerated concrete material of the present invention.
[0034] The recycled concrete aggregate used in the embodiment of the present invention is prepared by the following method: a cement paste sample with a water-cement ratio of 0.6 is used, and after standard curing for 90 days, it is crushed and sieved.
[0035] Example 1
[0036] (1) Recycled concrete aggregate (RCA) with a particle size of 0.6 to 1.18 mm was dried at 105°C, immersed in a 20 wt.% rust inhibitor (sodium monofluorophosphate) solution for 72 h, and then taken out and washed three times with deionized water to fully remove the rust inhibitor solution attached to the surface.
[0037] (2) The recycled concrete aggregate treated in step (1) is added to 100 mL of deionized water at a mass fraction of 5%, and stirred at 300 rpm for 30 min at room temperature; during the stirring process, carbon dioxide gas is injected into the mixed system to ensure that the recycled concrete aggregate is carbonized (the purity of carbon dioxide is 99.999%, the flow rate is 0.3 L / min, and the carbonization temperature is 25°C); after the carbonization is completed, the filter residue is collected by filtering with 2.5 μm filter paper, and the filter residue is freeze-dried at -50°C for 24 h to obtain a slow-release rust-resistant negative carbon recycled concrete material.
[0038] In order to characterize the CO2 capture effect of recycled concrete aggregate, TG test was carried out on the raw recycled concrete aggregate (RCA) of Example 1 and the recycled concrete aggregate (CRCA) after stirring for 2h after the introduction of CO2 (the purity of carbon dioxide was 99.999%, the flow rate was 0.3L / min, and the carbonization temperature was 25°C) without rust inhibitor loading. The TG-DTG curve is shown in Figure 1. Figure 2 .
[0039] from Figure 2 From the DTG results, it can be seen that the broad peak at 140°C in CRCA disappears, which is attributed to the separation of bound water in the CSH gel and AFm phase after carbonization. At the same time, the CH peak at 430°C almost disappears and a strong crystalline calcite endothermic peak appears, indicating that the CH phase is carbonized to generate a large amount of crystalline calcite. It should be noted that the endothermic peak of amorphous calcium carbonate at 690°C in RCA disappears, and a strong endothermic crystalline calcite peak appears at 740°C in CRCA, indicating that amorphous calcium carbonate undergoes a crystalline phase transformation after wet carbonization to generate stable highly crystalline calcite. The results confirm the CO2 capture performance of recycled aggregates.
[0040] Example 2
[0041] (1) Recycled concrete aggregate (RCA) with a particle size of 0.6 to 1.18 mm was dried at 105°C, immersed in a 20 wt.% rust inhibitor (sodium nitrite) solution for 72 h, then taken out and washed three times with deionized water to fully remove the rust inhibitor solution attached to the surface.
[0042] (2) The recycled concrete aggregate treated in step (1) was added to 100 mL of deionized water at a mass fraction of 5%, and stirred at 300 rpm for 30 min at room temperature; during the stirring process, carbon dioxide gas was injected into the mixed system to ensure carbonization of the recycled concrete aggregate (the purity of carbon dioxide was 99.999%, the flow rate was 0.1 L / min, and the carbonization temperature was 30°C); after the carbonization was completed, the solid was collected by filtration with 2.5 μm filter paper, and the solid was freeze-dried at -50°C for 24 h to obtain a slow-release rust-resistant negative carbon recycled concrete material.
[0043] Comparative Example 1
[0044] The only difference from Example 1 is that step (1) uses deionized water instead of the rust inhibitor solution to soak the recycled concrete aggregate; step (2) is the same as Example 1.
[0045] Example 3
[0046] The slow-release rust-resistant negative carbon regenerated concrete material (humidity 80%) prepared in Example 1 was used to replace the aggregate component (sand) to prepare mortar (calculated as RCA-PF group). The water-cement ratio of the mortar was 0.6, the cement-sand ratio was 1:3, and the replacement rate of the slow-release rust-resistant negative carbon regenerated concrete material was 50% Vol.
[0047] Among them, the lime-sand ratio is the mass ratio of cement: (sand + slow-release rust-resistant negative carbon recycled concrete material).
[0048] Example 4
[0049] The only difference from Example 3 is that the slow-release rust-resistant negative carbon regenerated concrete material prepared in Example 2 is used as a substitute, and the other conditions are the same as those in Example 3. It is counted as the RCA-CN group.
[0050] Control group
[0051] The only difference from Example 3 is that the deionized and soaked recycled concrete aggregate prepared in Comparative Example 1 is used as a substitute, and the other conditions are the same as those in Example 3. This is referred to as the RCA-O group.
[0052] The slow-release rust-resistant negative carbon regenerated concrete materials prepared in Examples 1-2 and Comparative Example 1 were dried and ground at 105° C., passed through a 75 μm sieve, and characterized by FTIR, TG, and XRD methods.
[0053] Figure 3 The compressive strength results of the slow-release rust-inhibiting negative carbon recycled concrete materials prepared in Examples 1-2 of the present invention and Comparative Example 1. Among them, the strength of the recycled concrete loaded with rust-inhibiting molecules is slightly improved compared with that of the concrete without rust-inhibiting molecules, which has a favorable effect on the basic mechanical properties of concrete.
[0054] Figure 4The FTIR graph (a), XRD graph (b), TG test result (c) of the slow-release anti-rust negative carbon regenerated concrete material prepared in Examples 1-2 and Comparative Example 1 of the present invention, and the test result of the conductivity (d) of the regenerated mortar obtained in Examples 3-4 and the control group. Among them, in (a)-(c), RCA-PF, RCA-CN and RCA-O correspond to the slow-release anti-rust negative carbon regenerated concrete materials of Example 1, Example 2 and Comparative Example 1, respectively; in (d), the RCA-PF group, RCA-CN group and RCA-O group correspond to the regenerated mortar of Example 3, Example 4 and the control group, respectively.
[0055] exist Figure 4 In (a), RCA-PF at 1037 cm -1 There is an obvious peak at 604 cm, which corresponds to the asymmetric stretching vibration of phosphate. -1 The peak at 1100cm in the RCA-PF is the in-plane bending vibration peak of the phosphate group, indicating that the sodium monofluorophosphate has migrated into the aggregate. The TG results show that the calcium hydroxide content in RCA-PF is significantly less than that in the control group, because calcium hydroxide reacts with sodium monofluorophosphate. The XRD results also show that the peak intensity of calcium hydroxide (CH) in RCA-PF is significantly weaker than that in the control group, confirming that part of the calcium hydroxide has been consumed by sodium monofluorophosphate. The FTIR results also show that the peak at 1100cm in RCA-PF is significantly weaker than that in the control group. -1 The peaks around 1271cm disappeared, which may indicate changes in the internal microstructure of the aggregate. Therefore, from the above analysis, it can be seen that sodium monofluorophosphate can effectively migrate into the recycled aggregate and cause changes in the internal microstructure of the aggregate. For the RCA-CN group samples, the peak at 1271cm in the FTIR spectrum -1 There is an obvious peak at , which corresponds to nitrite, proving that calcium nitrite has entered the interior of the aggregate. In the TG results, the broad peak at around 300°C proves that nitrite reacts with cement hydration products to generate NO2-AFM, and this phase can improve the internal microstructure of the recycled aggregate, which is also the reason why nitrite can improve the interface transition zone. The peak of RCA-CN at around 700°C is significantly stronger than that of other groups, mainly caused by excessive nitrite inside the aggregate. The internal ion concentration of the modified aggregate is generally higher than that of the control group, and its conductivity will also be higher than that of the control group, and Figure 4 (d) shows that the resistivity of the modified recycled mortar is higher than that of the control group. The resistivity of concrete is related to the pore solution and microstructure. Therefore, this phenomenon is mainly caused by the improvement of the recycled aggregate microstructure or interface microstructure by the rust inhibitor.
[0056] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A concrete, characterized in that: The aggregate in the concrete is replaced by 40-100% Vol using rust-resistant recycled concrete materials; the water-cement ratio of the concrete is 0.3-0.65, and the cement-sand ratio is 1:2-1:3; The rust-resistant recycled concrete material is obtained by carbonizing the recycled concrete material after loading the rust inhibitor; The method for preparing the rust-resistant recycled concrete material comprises the following steps: The recycled concrete material is soaked in a rust inhibitor solution, and then the soaked recycled concrete material is carbonized by a wet carbonization method, and filtered to obtain the rust-resistant recycled concrete material; The concentration of the rust inhibitor solution is 10-30%, and the immersion time is not less than 48 hours; The carbon dioxide flow rate of the wet carbonization method is 0.1-0.5 L / min, and the carbonization temperature is 20-30°C; The carbonization time of the wet carbonization method is 20-120 minutes.
2. The concrete according to claim 1, characterized in that After filtration, a drying step is also included.
Citation Information
Patent Citations
Carbon dioxide cured reinforced concrete and preparation method thereof
CN115521107A